Use of ABCD2 risk scoring system to determine the short-term stroke risk in patients presenting to emergency department with transient ischaemic attack - (:unkn) unknown (PAKISTAN MEDICAL ASSOC, 2013)
Objective: To determine the 3-day stroke risk of patients presenting to emergency department with transient ischaemic attack, and to evaluate the predictive value of ABCD(2) (Age, Blood pressure, Clinical features, Duration of symptoms and Diabetes) score for these patients. Methods: The prospective study was conducted on patients with diagnosis of transient ischaemic attack who were divided into low (0-3 points), medium (4-5 points) and high (6-7 points) risk groups according to their ABCD(2) scores. The sensitivity of the scoring system on estimation of the risk of stroke in 3 days was evaluated through receiver operating characteristic curve. SPS5 15 was used for data analysis. Results: Of the 64 patients in the study, none of the low-risk group had stroke. Stroke was present in 4 of 33 (12.12%) medium-risk patients, while there were 4 in 18 (22.22%) in the high-risk group. Sensitivity and specificity of each ABCD(2) score for 3rd day stroke risk was calculated. In the receiver operating curve generated by these calculations, the c statistics was determined as 0.76 (95% CI: 0.64, 0.86; p<0.01) and the most appropriate cut-off score to dichotomise the study group was determined as 4. Conclusions: In transient ischaemic attack patients with an ABCD(2) score of four or higher had a markedly increased short-term stroke risk, while those with a lower score were quite safe. It is appropriate to hospitalise patients with a score of four or more and investigate for underlying cause and initiate treatment.
Keywords: ABCD(2); Emergency department; Risk scoring system; Stroke risk; Transient ischaemic attack; VALIDATION; MANAGEMENT; DIAGNOSIS; STRATIFICATION; INTERVENTION; REFINEMENT; PREDICT